2006
DOI: 10.1128/jb.00080-06
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Metabolic Adjustments and Genome Plasticity Are Implicated in the Heat Shock Response of the Extremely Thermoacidophilic ArchaeonSulfolobus solfataricus

Abstract: Approximately one-third of the open reading frames encoded in the Sulfolobus solfataricus genome were differentially expressed within 5 min following an 80 to 90°C temperature shift at pH 4.0. This included many toxin-antitoxin loci and insertion elements, implicating a connection between genome plasticity and metabolic regulation in the early stages of stress response.The ability to cope with environmental stress is essential to microorganisms (1, 34, 39), including those thriving in extreme environments rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
102
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(118 citation statements)
references
References 55 publications
12
102
0
4
Order By: Relevance
“…5), whereas cells arrested by acetate showed elevated levels of Orc1-2 and low levels of Orc1-1 and Orc1-3 (1); resumption of growth after arrest resulted in elevated Orc1-1 and -3 and greatly reduced Orc1-2. Several laboratories have reported microarray analyses of the response of the Sulfolobus transcriptome to a range of physiological stresses such as UV treatment, viral infection, and heat shock (21)(22)(23)(24). Interestingly, these studies have revealed modulation of Orc1 gene transcript and/or protein levels; similar to that seen with microarray analysis of acetate-treated cells (25).…”
Section: Discussionsupporting
confidence: 48%
“…5), whereas cells arrested by acetate showed elevated levels of Orc1-2 and low levels of Orc1-1 and Orc1-3 (1); resumption of growth after arrest resulted in elevated Orc1-1 and -3 and greatly reduced Orc1-2. Several laboratories have reported microarray analyses of the response of the Sulfolobus transcriptome to a range of physiological stresses such as UV treatment, viral infection, and heat shock (21)(22)(23)(24). Interestingly, these studies have revealed modulation of Orc1 gene transcript and/or protein levels; similar to that seen with microarray analysis of acetate-treated cells (25).…”
Section: Discussionsupporting
confidence: 48%
“…In yeast, a heat shock transcription factor was found to coordinate expression of proteasome proteins to control proteasome synthesis under thermal stress, although the impact on this on CP constitution was not determined (18). Recent results from our lab showed that when S. solfataricus was shifted from optimal (80°C) to supraoptimal (90°C) temperatures, the transcription of ORFs encoding CP proteins (␣, ␤1, and ␤2) was unaffected throughout the 60-min period following the temperature shift (40). It was also noted that the transcriptional levels of CP proteins in S. solfataricus were much higher than in P. furiosus under normal or stressed conditions, although the ORF encoding S. solfataricus PAN decreased significantly following the temperature shift.…”
Section: Discussionmentioning
confidence: 97%
“…Additional components of the heat-shock (HS) response in this organism include adaptive heat resistance by pre-treatment (Trent et al 1990) and heat-induced shifts in the proteome (Cerchia et al 2000). In a related species, Sulfolobus solfataricus, the HS response transcriptome associated with a nonlethal temperature shift involved approximately one-third of the genome (Tachdjian and Kelly 2006). However, transcription factors that control thermotolerance are missing in crenarchaeotal genomes such as those characterized in the other major archaeal phylum, the Euryarchaeota (Thompson et al 1999;Vierke et al 2003;Liu et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, while VapC5 from several species of Mycobacteria have undergone structural (Miallau et al 2009) and in vivo characterization, a biologic function has yet to be identified (Robson et al 2009). In S. solfataricus, the strong and rapid heat-shock induction of certain vapBC loci (Tachdjian and Kelly 2006), combined with preliminary information on an uncomplemented vapBC mutant (Cooper et al 2009), provided the impetus to investigate the function of the toxin and antitoxin belonging to a single family member, vapBC6, and a role in thermotolerance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation